2020
DOI: 10.46266/njes.1015
|View full text |Cite
|
Sign up to set email alerts
|

Applying the sub-index model to evaluate the quality of water for irrigation purposes, a case study: wells water of left side from Mosul city, Iraq

Abstract: The present study aims to assess the quality of well water in some areas of the left side of Mosul city for irrigation; Water samples were collected from twelve wells scattered in the neighborhoods of Al-Muthana, Al-Zohoor, Al-Siddiq and Al-Hadba from November 2019 to January 2020 to measure the physical and chemical properties of wells and applying the subindicator model to evaluate the water quality. The results of the study indicated the suitability of well water quality for irrigation, where the WQI values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
7
1
Order By: Relevance
“…Excess salt can limit soil permeability; hence the sodium percentage was computed to offer information about the suitability of groundwater for irrigation [ 29 ]. Large levels of sodium in groundwater (over 60%) can generate sodium accumulations, disrupting soil formation [ 12 , 33 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess salt can limit soil permeability; hence the sodium percentage was computed to offer information about the suitability of groundwater for irrigation [ 29 ]. Large levels of sodium in groundwater (over 60%) can generate sodium accumulations, disrupting soil formation [ 12 , 33 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Irrigation water quality index is a technique for determining the suitability of plant life and soil constituents [ 12 , 36 ]. It has also been shown that the composite impacts the mineral constituents' effects in groundwater monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivity expresses the quantity and quality of ions dissolved in water (APHA, 2017), and the results shown in Table (3) indicate that the values fluctuated between (1040 -3712) µS. cm-1, and these differences are By the character of the geological formations through which the water passes, because the groundwater passing through the layers rich in evaporation salts is characterized by high salts values in them (Al-Hamdany, et al, 2020b). These values are less than the values obtained by Al-Saffawi (2019) in its study of water wells of the Al-Nimrud region at southeastern of Mosul city of Mosul city, which did reach to (5110) µS.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, using the IDW tool of Arcgis software version 10.2 (ESRI 1999), the spatial distribution of the estimated WQI values in the Essaouira basin was obtained. The model of the Irrigation Water Quality Index (IWQI) was created as a practical hydrogeological tool for assessing the overall quality of irrigation groundwater [61,62], as amended by Verma [63]. As shown in Table 3, eleven factors were used in the research region to assess water quality for irrigation purposes.…”
Section: Analytical Techniques and Groundwater Samplingmentioning
confidence: 99%
“…As shown in Table 3, eleven factors were used in the research region to assess water quality for irrigation purposes. Each attribute is given a weight based on its relative importance [61,62,64]. Because of its significance and influence on plant growth and soil quality, electrical conductivity, for example, is given a weighting of five.…”
Section: Analytical Techniques and Groundwater Samplingmentioning
confidence: 99%